Reskilling and Upskilling in the Digital Economy: Adaptive HRM Strategy in the Era of Industrial Revolution 5.0 - Munawaroh, Siti; Mustofa, Adhi; Raksajaya, Indra; Yuningrat, Nova; Tyas, Regita Anggia Ning (Journal of Village Development Innovation, 2025)
In the era of Industrial Revolution 5.0, rapid technological changes require workers to have relevant and adaptive skills. Reskilling and upskilling are becoming important strategies in human resource (HR) development to ensure organizational competitiveness. However, the biggest challenge is how to design and implement effective training programs to deal with these changes. This study aims to explore and analyze how adaptive strategies in human resource management (HRM) can support the implementation of effective reskilling and upskilling programs in the digital era and Industrial Revolution 5.0. This study used a descriptive qualitative approach, with data collection methods through in-depth interviews and questionnaires distributed to HRM professionals and employees in companies that have implemented skills training programs. This study found that companies that successfully implemented reskilling and upskilling programs experienced increased productivity and competitiveness. The success of these programs relies heavily on managerial support, an organizational culture that supports learning, and adaptive leadership that is actively involved in the planning and evaluation of training programs. Reskilling and upskilling programs designed with HRM adaptive strategies can improve workforce competencies and organizational competitiveness. Organizations need to ensure full support from management and proactive leadership in supporting employee skills development to remain relevant in the face of technological challenges.